Variability of slot size in orthodontic brackets - Clémentine Lefebvre; Hassan Saadaoui; Jean‐Marc Olive; Stéphane Renaudin; Fabienne Jordana (Wiley, 2019)
Abstract Objective The accuracy of the information incorporated into brackets is a determining factor for the efficacy of torque applied to teeth. The aim of this study was to compare the dimensions of a bracket's slots with the nominal values announced by the manufacturer. Materials and methods A total of 730 maxillary right central brackets manufactured by seven companies (Dentsply Gac, American Orthodontics, Rocky Mountain Orthodontics, GC Orthodontics, 3M Unitek, and Dentaurum) were studied. The sample included 0.018 × 0.025 and 0.022 × 0.028 in., metal and ceramic, conventional and self‐ligating brackets. Images were obtained with an Olympus BX51 optical microscope. Slot dimensions were measured at the base and at the face on both mesial and distal sides using ImageJ software. Data were analyzed using Wilcoxon, sign tests, two‐ and three‐way ANOVA, and Tukey's tests. Intraclass correlation coefficient was employed to assess the intraobserver and interobserver variability. The threshold for statistical significance was p ≤ .05. Results Statistical analysis showed that the slot dimensions of 90% to 97% of studied brackets were significantly different from nominal values. In general, slot size was oversized, with a face size larger than the base size. Comparison between mesial and distal sides showed that up to 45% of the brackets were significantly asymmetrical. The manufacturer had a significant effect for base and face widths (p = .0001) and for length (p = .003). Conclusion This study shows that a large proportion of measured brackets displays dimensional inaccuracies when compared with stated values. Clinically, the slot oversize and the divergence of slot walls cause an increase of wire‐slot play, inducing a loss of torque control. Practitioners cannot fully trust the precision of used appliances and should be aware that adjustments could be needed in the finishing stages of the treatment.